NUMERICAL INVESTIGATIONS ON THE DYNAMIC BEHAVIOUR OF A 2-DOF AIRFOIL WITH APPLICATION IN ENERGY HARVESTING SYSTEM - Tomasz HANISZEWSKI; Damian GĄSKA; Jerzy MARGIELEWICZ; Tadeusz OPASIAK (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents the basic airfoil model with two degrees of freedom - the semi-rigid model, where its forced vibrations were considered, and the exciting force is the aerodynamic force, including its periodic changes, that is, gusts. Since the phenomenological model under study has a coupled form, its versions after decoupling are presented, which has an impact on the results of the final research. The airfoil model presented in this way was shown from the application side in the system of a simple energy harvester based on a deformable beam with piezoelectric elements. The result of the simulation tests is a preliminary analysis of the possibility of using the airfoil as a vibration generator for the energy harvesting system. Along with the application of the mechanical part, a numerical simulation of the electrical part was also implemented, related to the transformation of the voltage generated by piezoelectric elements into a constant voltage signal with a connected receiver with power consumption similar to the Atmega microcontroller with battery charging.